2019
DOI: 10.15760/trec.218
|View full text |Cite
|
Sign up to set email alerts
|

Transferability & Forecasting of the Pedestrian Index of the Environment (PIE) for Modeling Applications

Abstract: This project focuses on making our measures, models, and methods more transferable to other locations. Specifically, we re-evaluate, compare and test our pedestrian index of the environment (PIE) measure using data resources more commonly available to planning agencies across the country. Next, we test the results of PIE and its input data in models of pedestrian mode choice for stability of estimation results within a region (intraregional) and between regions (interregional). This research is the next logica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…MoPeD provides the pedestrian modeling framework in this work. MoPeD was initially developed by Clifton et al (2015Clifton et al ( , 2016aClifton et al ( , 2016bClifton et al ( , 2019 and then further enhanced by Zhang et al (2021). The previous work on MoPeD showed that this tool is sensitive to the small-scale variations in local land use and transport development, and it is capable to assess the planning policies on a regional scale (Zhang et al 2021).…”
Section: Pedestrian Modeling Framework: Mopedmentioning
confidence: 99%
“…MoPeD provides the pedestrian modeling framework in this work. MoPeD was initially developed by Clifton et al (2015Clifton et al ( , 2016aClifton et al ( , 2016bClifton et al ( , 2019 and then further enhanced by Zhang et al (2021). The previous work on MoPeD showed that this tool is sensitive to the small-scale variations in local land use and transport development, and it is capable to assess the planning policies on a regional scale (Zhang et al 2021).…”
Section: Pedestrian Modeling Framework: Mopedmentioning
confidence: 99%
“…In this study, we adopt the framework of MoPeD to quantify the impact of land use and transportation policies on walking behavior. MoPeD was described by Clifton et al, (2015Clifton et al, ( , 2016aClifton et al, ( , 2016bClifton et al, ( , 2019. The framework of MoPeD is illustrated in Figure 1.…”
Section: Moped Model Descriptionmentioning
confidence: 99%
“…In this study, pedestrian route choices were added to this modeling suite using the shortest path algorithm. We enhanced the model performance and made some modifications to the model stages from the version previously described by Clifton et al (2015Clifton et al ( , 2016aClifton et al ( , 2016bClifton et al ( , 2019. These improvements were made to overcome the following limitations:…”
Section: Moped Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The form of the cost function and its parameters have a significant impact on the indicator value, mainly for journeys by public and multimodal transport ( 26 ). As the selection of an accessibility indicator largely depends on the purpose, several studies have aimed at assessing the different indicators for different planning purposes ( 27 30 ). Yet, these studies have mainly focused on accessibility to destinations such as jobs and local amenities.…”
Section: Literature Reviewmentioning
confidence: 99%